An asymptomatic case report with Prolonged Viral Clearance: an issue to ponder COVID-19 control and containment - Sultana, Shahnaz; Saha, Avirup; Khan, Shakila Nargis; Karim, Muhammad Manjurul (Bangladesh Journal of Medical Science, 2021)
A 58-year-old man was tested positive for COVID-19 with mild clinical symptoms. Although symptoms resolved within 2 days, the patient was tested positive again on day 29 post-illness after a negative test. It took more than 40 days to become a negative carrier of SARS-CoV-2. Such asymptomatic cases raise questions on the recommended isolation period. If not contained, these asymptomatic carriers could create challenges for disease control by allowing infection back to the community. A lengthened isolation of patients with COVID-19 for 6 weeks postillness could be a safeguard for the community. Bangladesh Journal of Medical Science Vol.20(1) 2021 p.187-189